Maternal Employment, Child’s Caring Practices and Nutritional Status in Northern Ghana - Aguree, Sixtus; Ziem, Juventus B.; Issah, Amos; Akrugu, Theophilus; Joseph, Ali (International Journal of Child Health and Nutrition, 2015)
Mothers as caregivers exert strong influence over child feeding and caring practices. Maternal employment may influence child caring practices thus affecting the child’s nutritional status. The purpose of this study was to examine the effect of maternal employment status, on child caring practices and the nutritional status of children under-5 in Savelugu, Northern Ghana. This was a cross-sectional survey involving 400 mothers and their children under-5 years old. Data collection took place between February and May, 2013 through a house-to-house visit using a structured questionnaire designed for the study. Information collected included employment status, occupation type and mothers working hours away from home, feeding and caring practices and anthropometric measurements of their children. About 85.8% of respondents were employed. Together farmers and traders made approximately 76% of the respondents. Approximately 55% of Mothers had at least primary education. Around 85.1% of the employed mothers look after their children whiles carrying out their daily work. Employed mothers spent between 5 to 6 hours/day away from home without their children but unemployed mothers were mostly with their children. Occupation status has a significant effect on child caring practices with those unemployed being better (P<0.05). About 72.0% and 70.3% respectively of unemployed and employed mothers indicated they introduced complementary feeding at 6months. Child caring practices were better among unemployed mothers compared to employed mothers among the study population. Stunting and wasting rates were high among children of both employed and unemployed mothers.